Comparison of three methods for in vivo quantification of glutathione in tissues of hypertensive rats. (2nd December 2021) - Kalinovic, Sanela; Stamm, Paul; Oelze, Matthias; Daub, Steffen; Kröller-Schön, Swenja; Kvandova, Miroslava; Steven, Sebastian; Münzel, Thomas; Daiber, Andreas
Abstract: Glutathione (γ-L-glutamyl-L-cysteinyl-glycine, GSH) is a tripeptide that is part of the antioxidant defense system and contributes to numerous redox-regulatory processes. In vivo, reduced GSH and oxidized glutathione disulfide (GSSG) are present in redox equilibrium and their ratio provides important information on the cellular redox state. Here, we compared three different methods for in vivo quantification of glutathione in tissues of hypertensive rats, an accepted animal model of oxidative stress. In the present study, we used hypertensive rats (infusion of 1 mg/kg/d angiotensin-II for 7 days) to determine the levels of reduced GSH and/or GSH/GSSG ratios in different tissue samples. We used an HPLC-based method with direct electrochemical detection (HPLC/ECD) and compared it with Ellman's reagent (DTNB) dependent derivatization of reduced GSH to the GS-NTB adduct and free NTB (UV/Vis HPLC) as well as with a commercial GSH/GSSG assay (Oxiselect). Whereas all three methods indicated overall a decreased redox state in hypertensive rats, the assays based on HPLC/ECD and DTNB derivatization provided the most significant differences. We applied a direct, fast and sensitive method for electrochemical GSH detection in tissues from hypertensive animals, and confirmed its reliability for in vivo measurements by head-to-head comparison with two other established assays. The HPLC/ECD but not DTNB and Oxiselect assays yielded quantitative GSH data but all three assays reflected nicely the qualitative redox changes and functional impairment in hypertensive rats. However, especially our GSH/GSSG values are lower than reported by others pointing to problems in the work-up protocol.